Pharmaceutical Development of Intraperitoneal Arachis hypogaea as a Renal Protective Agent - Gul, Arab; Khan, Haroon; Shah, Sayyed Ibrahim; Alsharif, Khalaf F.; Qahl, Safa H.; Rehman, Inayat Ur; Goh, Khang Wen; Ardianto, Chrismawan; Long, Chiau Ming * (IMR Press, 2023)
Background: Kidneys are among the vital organs of the human body; therefore, damage from any exogenous/endogenous agent may put human life at risk. Arachis hypogaea (AH) contains different free radical scavenging flavonoids, stilbenes, and tannins. This research aimed to elucidate the possible nephroprotective mechanism of AH methanolic crude extract (AHcr) and n-hexane oil fraction (AHO) against gentamycin-induced nephrotoxicity.